Thermionic Energy Conversion in the Twenty-first Century: Advances and Opportunities for Space and Terrestrial Applications - Go, David B.; Haase, John R.; George, Jeffrey; Mannhart, Jochen; Wanke, Robin; Nojeh, Alireza; Nemanich, Robert (Frontiers in Mechanical Engineering, 2017)
Thermionic energy conversion is the direct conversion of heat into electricity by the mechanism of thermionic emission, the spontaneous ejection of hot electrons from a surface. Although the physical mechanism has been known for over a century, it has yet to be consistently realized in a manner practical for large-scale deployment. This perspective article provides an assessment of the potential of thermionic energy conversion systems for space and terrestrial applications in the 21st century, overviewing recent advances in the field and identifying key research challenges. Recent developments as well as persisting research needs in materials, device design, fundamental understanding, and testing and validation are discussed.